Perencanaan Strategis Sistem Informasi dan Teknologi Informasi pada STIE Pertiba Pangkalpinang - Priambodo, Nugroho Yoga; Suroso, Jarot S. (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
As one of the pioneers of the STIE Pertiba Pangkalpinang management study program, it strives to continuously improve its competitiveness and strategic advantage compared to other similar high schools, STIE Pertiba Pangkalpinang must have a Strategic Planning of Information Systems and Information Technology that is in line with the organization's vision and mission. The purpose of this research is to develop the IS/IT needs of STIE Pertiba Pangkalpinang to support public services, academics, students, lecturers and staff at STIE Pertiba Pangkalpinang. This study uses a qualitative descriptive research using the Ward and Peppard framework with several analytical tools to analyze the external environment with PEST and Porter Five Forces, the Internal Business Environment with SWOT, CSF and Value Chain, External IS/IT Environmental Analysis with IS Technology Trends. Latest IT and Internal IS/IT Environmental Analysis with McFarlan Grids Analysis. The results show that the Ward and Peppard Frameworks can see various perspectives of the company in terms of internal and external strengths and weaknesses on the business side or IS/IT, so they can identify future IS/IT portfolio needs required by the company through the IS/IT business strategy process. IT, IS/IT management and IT strategy. And produced 3 (three) strategies, namely IS business strategy, IS/IT Management Strategy and IT strategy to help STIE Pertiba Pangkalpinang increase its competitive advantage.